2011
DOI: 10.3945/ajcn.110.009399
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resting and walking energy expenditure and walking speed during pregnancy in obese women

Abstract: Background: Energy-conserving processes reported in undernourished women during pregnancy are a recognized strategy for providing the energy required to support fetal development. Women who are obese before conceiving arguably have sufficient fat stores to support the energy demands of pregnancy without the need to provoke energy-conserving mechanisms. Objective: We tested the hypothesis that obese women would show behavioral adaptation [ie, a decrease in self-selected walking (SSW) speed] but not metabolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
(82 reference statements)
3
32
1
Order By: Relevance
“…In our study, there was an overall increase in REE throughout the study of 11.5%. This is similar to other studies that have assessed REE that found increases ranging from 13% to 35% [8,11,[15][16][17]. The large range in changes in REE throughout pregnancy is reflective of the population being studied, the body weight status prior to the study, and the duration of data collection (e.g., preconception to postpartum).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, there was an overall increase in REE throughout the study of 11.5%. This is similar to other studies that have assessed REE that found increases ranging from 13% to 35% [8,11,[15][16][17]. The large range in changes in REE throughout pregnancy is reflective of the population being studied, the body weight status prior to the study, and the duration of data collection (e.g., preconception to postpartum).…”
Section: Discussionsupporting
confidence: 85%
“…Real-time, mobile tracking of REE has become increasingly popular but few devices are able to accurately estimate caloric needs [12]; further, they have rarely been used in pregnant populations [13,14]. Changes in REE during pregnancy have demonstrated an overall increase in caloric needs [8,11,[15][16][17] ranging from 13-35%. Recently, the Breezing™ device, a hand-held, Bluetooth-enabled metabolism tracker, that uses indirect calorimetry to measure REE was developed and validated against the laboratory-based Douglas Bag Method [18].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown in obese pregnant women that, over gestation, the energy cost of movement can decrease, and that this is because of both behavioural (walking more slowly) and biological (improved walking economy) compensations. 38 Further, we, and others, have shown reductions in non-exercise activity thermogenesis in overweight and obese individuals in response to exercise training and/or caloric restriction interventions. [39][40][41] Given that accurate measurement of daily physical activity and activity energy expenditure can be challenging in studies of freeliving humans, it is useful to consider evidence from highlycontrolled animal studies.…”
Section: Discussionmentioning
confidence: 72%
“…Importantly, the dynamic changes that occur in biological and behavioural adaptations to pregnancy are complex and difficult to capture using simple measures at a few time points. Others have documented increases in resting energy expenditure accompanied by even larger decreases in physical activity-related energy expenditure in pregnancy,5 6 although dietary intake measurements were not made in these studies.…”
Section: Commentarymentioning
confidence: 85%